A Dixonian analysis of petrol retailing in the U.K. – 1880-2000. Issue 4 (8th August 2017) - Ritson, Neil H.; Byrne, Ian W.; Cohen, David A.
Abstract: The development of the retail petroleum industry in the U.K. has received only sporadic attention by academics. Whilst the retail petroleum industry in the U.K. is usually thought of as an oligopoly, with a small number of companies controlling the production and movement of products through vertical integration, there is evidence of significant high-level changes in the global industry resulting in the loss of retailing sites belonging to the major companies, and a rise in the number and influence of competitors. These constitute both multiple retailers such as supermarket chains, and at the 'competitive fringe', a rise in the number of smaller independents. In this paper, we identify the changes and then analyse the factors underlying them using the Dixonian system model of macromarketing. In contrast to the usual fine-grained approach of the marketing mix, the Dixonian system comprises an hierarchical, systematic view of the product market which suits an analysis of the complexity of the factors in this sector.